Beyond traditional wage premium: An analysis of wage greenium in Latin America - Manuela Cerimelo; Pablo de la Vega; Natalia Porto; Franco Vazquez (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2024)
This paper estimates wage differentials between green and non-green jobs (wage greenium) in nine major Latin American countries (Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Peru and Uruguay), which account for 81% of the region's GDP. We contribute to the recent literature highlighting a positive wage gap for those working in green jobs in developed countries. A positive wage gap for green jobs may be a virtuous market feature, as it means that in the future workers might be encouraged to switch to greener occupations. To do so, we define green jobs as those occupations with high greenness scores using the occupational approach as in Vona et al. (2018), Vona (2021) and de la Vega et al. (2024). Our results suggest that the wage greenium for the period 2012-2019 in Latin America was between 18% to 22%. Moreover, this wage gap has remained relatively stable over the years.
Keywords: E24; Q50; J31; 330; labor markets; green jobs; wage premium; wage differentials; Latin America